Lewis acid-mediated β-selective hydrocarboxylation of α, α-diaryl- and α-arylalkenes with R3SiH and CO2. Issue 24 (10th June 2015) - Tanaka, Shinya; Tanaka, Yuuki; Chiba, Masafumi; Hattori, Tetsutaro
Graphical abstract: Abstract: α, α-Diarylalkenes are successfully hydrocarboxylated with Et3 SiH and CO2 with the aid of Et3 SiB(C6 F5 )4 or EtAlCl2 /Ph3 SiCl to give carboxylic acids with a carboxy group at the β-position to the aryl groups. The EtAlCl2 /Ph3 SiCl-mediated reaction is also applicable to various α-arylalkenes. 1 H NMR analysis of a mixture of EtAlCl2, Ph3 SiCl, and Et3 SiH strongly suggests the formation of a μ -H complex, [Ph3 Si–H–SiEt3 ] + AlEtCl3 −, which is an equivalent of R3 Si + ions, while Et3 SiB(C6 F5 )4 is an ion pair with a Et3 Si + ion. Therefore, in these reaction systems, a siloxycarbonylium, R3 SiOCO +, is considered to be a common electrophile, the addition of which to the substrate, followed by trapping of the resulting cationic species with Et3 SiH seems to afford the desired acid after aqueous workup.